Phytochemical and biological analysis of medicinal plant, apium graveolens (celery): a review / Rohaiza Saat and Nor Amira Ishak - Saat, Rohaiza; Ishak, Nor Amira (Faculty of Plantation and Agrotechnology, 2023)
Apium graveolens, popularly known as celery, is a medicinal plant used in traditional medicine to treat various types of diseases due to the presence of a variety of active compounds. The stem, leave, seed, and root of A. graveolens are rich in antioxidant flavonoids, including apigenin and apiin. Apigenin is known can enhance adult neurogenesis, improve blood glucose levels, and antioxidant levels. Meanwhile, apiin can increase the activity of detoxifying enzymes such as superoxide dismutase (SOD), glutathione (GSH) peroxidase, and catalase. Bioactive compounds known as phthalides can also protect against cancer, high blood pressure, and cholesterol. Hence, the presence of these various bioactive molecules in A. graveolens have shown antioxidants, anti-inflammatory, and other biological activities. For the past ten years, several discoveries have also been made regarding the medicinal properties of these herbs. As a result, in this review, we provide an overview of recent research on the various uses, phytochemistry, and biological activity found in all parts of A. graveolens species to discuss its medical value and potential application in complementary and alternative medicine. This review aims to give current knowledge and perspectives on A. graveolens as a therapeutic herb.